Developing a Model for an Innovative Culinary Competency Curriculum and Examining Its Effects on Students' Performance. (17th February 2016) - Hu, Meng‐Lei I‐Chen Monica; Horng, Jeou‐Shyan; Teng, Chih‐Ching
Abstract: The present study designs and develops an innovative culinary competency curriculum (ICCC) model comprising seven sections: innovative culture, aesthetics, techniques, service, product, management, and creativity. The model is formulated based on culinary concept, creativity, innovation, and competency theory. The four elements of curriculum design, namely, objectives, learning experience, evaluation, and modification, are adopted to create a developmental framework. This study also applies creative teaching techniques to improve students' learning effectiveness. The study employed a quasi‐experimental design and a sample of 68 undergraduate students majoring in Food and Beverage Management. A 16‐week instructional program was conducted. Results show that the ICCC model is effective based on qualitative analysis and students' improved innovative performance.